Analysing first grade teachers' strategies for enhancing English reading proficiency in multilingual classroom environments in Namibia - Strauss, Annaly Magda (Revija za elementarno izobraževanje, 2024)
The study aims to analyse how primary school teachers of Grade 1 develop reading skills in multilingual classroom settings in Namibia. A case study approach was adopted to collect data through interviews and classroom observations. The findings reveal that teachers do not model a structured or systematic approach to scaffold learners during reading lessons. They rather rely on the translation method to foster learners' understanding of reading texts in multilingual contexts and rarely use differentiated activities. This calls for new more learner-centred approaches towards developing reading which would allow for more pronounced learners' perspectives of reading in multilingual contexts.
Keywords: developing reading competence; didactic approaches; didaktični pristopi; medjezikovno preklapljanje; multilingual environment; razvijanje bralne kompetence; translanguaging; večjezično okolje; Večjezičnost